Implementasi Kebijakan Bagi Masyarakat Dalam Memilih di Indonesia - Aprilla Haryanti; Nazwa Aura Rahmadhani; Mutia Arifah; Ilham Hudi; Hasiela Nurfajrina Seprizal; Ray Febisya Thawil Wahid (International Forum of Researchers and Lecturers, 2024)
General elections or what can be called people’s democratic parties are one of the main parameters for measuring the success of implementing democracy in a country. This research discusses the relationship between society and the state in voting, characterized by Indonesia being a country that adheres to a democratic system, where state power is in the hands of the people, as regulated in the 1945 Constitution of the Republic of Indonesia. The aim is to know and understand how to implement it. Public policy in voting in Indonesia. Method was carried out using a literature approach. The results of the research are to understand the public policy system in voting in Indonesia and how the government behaves in dealing with problems wisely during elections, and democracy can run well in accordance with its principles and objectives. The results of this research show that whenever there are problems when voting, the right policies will be able to minimize the problems that occur. The policies that need to be implemented are in accordance with government regulations and the principles of democracy itself.